Targeting of pancreatic and prostate cancer stem cell characteristics by Crambe crambe marine sponge extract - Ottinger, Sabine; Rausch, Vanessa; Liu, Li; Kallifatidis, Georgios; Gross, Wolfgang; Gebhard, Martha-Maria; Herr, Ingrid (International journal of cancer, 2012)
Cancer stem cells (CSCs) are suggested as reason for resistance of tumors toward conventional tumor therapy including pancreatic and advanced prostate cancer. New therapeutic agents are urgently needed for targeting of CSCs. Marine sponges harbor novel and undefined compounds with antineoplastic activity but their potential to eliminate CSC characteristics is not examined so far. We collected 10 marine sponges and one freshwater sponge by diving at the seaside and prepared crude methanolic extracts. The effect to established pancreatic and prostate CSC lines was evaluated by analysis of apoptosis, cell cycle, side population, colony and spheroid formation, migratory potential in vitro and tumorigenicity in vivo. While each sponge extract at a 1:10 dilution efficiently diminished viability, Crambe crambe marine sponge extract (CR) still strongly reduced viability of tumor cells at a dilution of 1:1,000 but was less toxic to normal fibroblasts and endothelial cells. CR inhibited self-renewal capacity, apoptosis resistance, and proliferation even in gemcitabine-selected pancreatic cancer cells with acquired therapy resistance and enhanced CSC characteristics. CR pretreatment of tumor cells diminished tumorigenicity of gemcitabine-resistant tumor cells in mice and totally abolished tumor take upon combination with gemcitabine. Our data suggest that CR contains substances, which render standard cancer therapy more effective by targeting of CSC characteristics. Isolation of bioactive metabolites from CR and evaluation in mice are required for development of new CSC-specific chemotherapeutic drugs from a marine sponge.
Published online: 4 May 2011
Gesehen am 23.04.2018